Depolarization ratio for randomly oriented ice crystals of cirrus clouds - Kustova, Natalia V.; Konoshonkin, Alexander V.; Shishko, Viсtor A.; Timofeev, Dmitriy N.; Tkachev, Ilya V.; Wang, Zhenzhu; Borovoi, Anatoli G. (Atmosphere)
The depolarization ratio and backscattering cross sections have been calculated for shapes and size of ice crystals that are typical in cirrus clouds. The calculations are performed in the physical-optics approximation. It is shown that the depolarization ratio approaches some constant when the size of the crystals becomes much larger than the incident wavelength. For the transparent ice crystals, when absorption is absent, the magnitude of this constant strongly depends on crystal shapes. This fact allows inferring the crystal shape from magnitudes of the depolarization ratio in lidar signals. For the lidar wavelengths, where absorption of light is considerable, the depolarization ratio of lidar signals can be used for inferring crystal sizes. Such results are important for the development of algorithms interpreting the signals obtained by both ground-based and space-borne lidars.